Moderation of Leadership Style: Management Accounting Information Systems and Management Control Systems on Managerial Performance - Edi Jusriadi (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine and analyze the effect of management accounting information systems and control systems on managerial performance with leadership style as a moderating variable at PT. Pa'baeng-baeng branch pawnshop. The data collection technique used in this research is the survey technique by distributing questionnaires and studying documentation. The population and samples used in this study were 30 respondents. The data analysis technique used is multiple linear regression analysis were processed using assistance Software SPSS26. This study indicates that the management accounting information system and control system have a positive and significant effect on managerial performance at PT. Pa'baeng-baeng branch pawnshop. These results suggest that the leadership style variable only weakens the influence of the management accounting information system and management control system on organizational performance at PT. Pa'baeng-baeng branch pawnshop. The company is expected to maintain and carry out its functions systematically so that the management accounting information system and management control system can run effectively. The company is also likely to continue improving managerial performance with variables other than the management accounting information system and control systems, such as performance measurement system variables, information technology, etc. For further researchers, this research is expected to be used as a reference to be used as material for research development by using other variables outside of this research and using more and more varied research indicators and adapted to the situation and condition of the object of study.